2001
DOI: 10.1046/j.1440-1819.2001.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

An open pilot trial of olanzapine for delirium in the Korean population

Abstract: This study was performed to assess the efficacy and safety of olanzapine for the treatment of delirium in a Korean population. An open trial of olanzapine was conducted in Korean patients with delirium caused by multiple medicosurgical conditions. All subjects were evaluated by Delirium Rating Scale (DRS), which is known to be one of the most sensitive scales for delirium. In addition, other data for profiles of side-effects were collected and analyzed. Twenty patients were treated by olanzapine with doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 23 publications
0
34
0
6
Order By: Relevance
“…The usefulness of new atypical antipsychotics has been debated in the literature. Some evidence indicate that olanzapine [118][119][120][121] and quetiapine [122] have efficacy similar to that of haloperidol, with fewer side effects, in delirious patients; risperidone showed similar efficacy and side effects [123]. Numerous authors advocate that results from trials in dementia patients suffering from behavioral and psychological symptoms allow the recommendation of new atypical antipsychotics in delirium.…”
Section: Investigation and Treatmentmentioning
confidence: 99%
“…The usefulness of new atypical antipsychotics has been debated in the literature. Some evidence indicate that olanzapine [118][119][120][121] and quetiapine [122] have efficacy similar to that of haloperidol, with fewer side effects, in delirious patients; risperidone showed similar efficacy and side effects [123]. Numerous authors advocate that results from trials in dementia patients suffering from behavioral and psychological symptoms allow the recommendation of new atypical antipsychotics in delirium.…”
Section: Investigation and Treatmentmentioning
confidence: 99%
“…The current literature on atypical antipsychotic use in delirium is limited to open trials, case reports and reviews. Thus, the authors cannot recommend this drug class as first-line treatment for delirium symptoms but several reports suggest their efficacy and safety [81][82][83][84][85][86][87]. A further reason why the authors are less enthusiastic about the use of atypical antipsychotics is that, with the very recent exception of ziprasidone (Geodon ® , Pfizer Inc., NY, USA), (now available intramuscularly), none of these drugs are available in parenteral form, thus complicating or preventing their administration to some agitated or combative patients.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, several studies using both prospective (Horikawa et al, 2003;Kim et al, 2001;Breitbart et al, 2002) and retrospective methods (Sipahimalani and Masand, 1998) demonstrated that risperidone and olanzapine, which have superior pharmacological profiles in lowering the EPS via a simultaneous blockade of the serotonin and dopamine receptors, could be alternative agents to typical antipsychotics in the treatment of delirium. The efficacy and safety of quetiapine for treating delirium was also examined in case reports (Al-Samarrai et al, 2003;Torres et al, 2001), a retrospective chart review (Schwartz and Masand, 2000) and an open trial with a small sample (Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%